Lactitol and β‐cyclodextrin alleviate the intensity of goaty flavor. (15th November 2022) - Ma, Yue; Li, Jinzhe; Liu, Yue; Dou, Nianxu; Mu, Sinan; Wei, Xuan; Bilawal, Akhunzada; Hou, Juncai; Jiang, Zhanmei
Abstract: BACKGROUND: Goat milk has balanced nutritional composition, is conducive to digestion and absorption, and does not easily lead to allergic reactions. However, the special goaty flavor in milk has seriously affected consumer acceptance. It is imperative to alleviate the goaty flavor in a safe and efficient way. RESULTS: This study indicated that the supplementation of 6 g kg −1 β‐cyclodextrin or 8 g kg −1 lactitol in goat milk significantly alleviated goaty flavor and improved sensory characteristics. Furthermore, the supplementation of β‐cyclodextrin and lactitol had a synergistic effect in reducing the content of free fatty acids that cause goaty flavor. The content of caproic acid (C6 H12 O2 ), octanoic acid (C8 H6 O2 ), and decanoic acid (C10 H20 O2 ) decreased by 42.46%, 39.45%, and 46.41%, respectively, after a combined group was supplemented with 6 g kg −1 β‐cyclodextrin and 7 g kg −1 lactitol, which was significantly lower than in groups given β‐cyclodextrin or lactitol individually. CONCLUSION: This study provides a novel and effective approach to alleviate goaty flavor and promote the competitiveness of goat milk products. © 2022 Society of Chemical Industry.